Dynamics Of Authority To Defend The Kanjuruhan Tragedy In The Criminal Justice System (DiH: Jurnal Ilmu Hukum, 2023)
The Criminal Justice System in Indonesia has explained related to the authority of each law enforcement apparatus, including the authority to defend suspects or defendants. However, deviations occurred in 2022 where the police acted as defenders in trials (legal advisors) for other members of the police who were accused in the Kanjuruhan tragedy, this is of course vulnerable to conflicts of interest and is not in line with the criminal justice system. The research method used is empirical juridical, which is related to the implementation of laws and regulations in cases that occur in society, in this case, the question of the authority to defend in the trial of the Kanjuruhan case. In principle, the authority to defend in the context of criminal justice is regulated in the Law No.18/2003, in cases where a police officer is acting as a legal representative for other police officers in criminal cases it is a deviation from the process of the criminal justice system in Indonesia, this also contradicts Article 16 in the Law No.2/2002, which explains that the police do not have the authority to provide legal assistance in criminal trials. Keywords: authority; criminal justice system; defense